2018
DOI: 10.3892/etm.2018.7044
|View full text |Cite
|
Sign up to set email alerts
|

Nrf2 overexpression protects against paraquat‑induced A549 cell injury primarily by upregulating P‑glycoprotein and reducing intracellular paraquat accumulation

Abstract: Paraquat (PQ) intoxication causes thousands of mortalities every year, worldwide. Its pulmonary-targeted accumulation and the acute lung injury it subsequently causes, remain a challenge for detoxification treatment. A previous study has demonstrated that the upregulation of nuclear factor erythroid-2 related factor 2 (Nrf2) prevents PQ toxicity in cell line and murine models. As Nrf2 target genes include a group of membrane transporters, the current study assessed the protective mechanism exerted by Nrf2 agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…These features confirm the critical role of Nrf2 in the control of resistance in cancer cells in response to chemotherapeutic agents. In line with our results, Payandeh et al 29,30 33 In another study, Exo harboring ubiquitin carboxy-terminal hydrolase-L1-mediated adriamycin resistance in breast cancer cells. 34 Concerning drug resistance in CC, several different proteins have been identified.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These features confirm the critical role of Nrf2 in the control of resistance in cancer cells in response to chemotherapeutic agents. In line with our results, Payandeh et al 29,30 33 In another study, Exo harboring ubiquitin carboxy-terminal hydrolase-L1-mediated adriamycin resistance in breast cancer cells. 34 Concerning drug resistance in CC, several different proteins have been identified.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to our results, Zhang et al 32 showed that exosomal transfer of p‐STAT3 confers 5‐fluorouracil resistance in colorectal cancer cells. It has been shown that Exo‐mediated transfer of chloride intracellular channel 1 increases vincristine resistance in gastric cancers 33 . In another study, Exo harboring ubiquitin carboxy‐terminal hydrolase‐L1‐mediated adriamycin resistance in breast cancer cells 34 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These are essentially electrostatic interactions due to the negatively Regarding PQ and GEN compounds, even though the experimental transport assay results in Figure 11 show that these compounds at 50 µM do not interfere with the P-gp mediated efflux of R123 out of Caco-2 cells, the estimated binding energies have very favorable values. The literature available reveals different results regarding PQ and P-gp interaction (e.g., some authors stated that PQ is transported by P-gp [58] while others stated that it is not a P-gp substrate [59]). In the resulting binding pose (Figure 19), PQ forms hydrophobic interactions involving four residues in the binding pocket (Y310, F314, F728, and 732), all of them π-π type of interaction.…”
Section: Name Hydrogen Bondmentioning
confidence: 99%
“…Importantly, more recent researches have expounded that Nrf2 played an essential role in the regulation of oxidative stress and Nrf2 activation is a key event throughout the development of PQ poisoning [ 28 ]. Based on the in vivo and in vitro results, we also proved that Nrf2 was mainly in the cytoplasm of cells rather than in nucleus under unstressed conditions.…”
Section: Discussionmentioning
confidence: 99%